Cross-cultural crisis intervention training via videoconferencing. (September 2015) - Wyatt, Jeannette; Silver, Paula
This article describes the training of Chinese social work faculty and professionals in crisis intervention in order to assist them in applying crisis intervention skills to their work with earthquake victims in their region and develop the capacity for future relief efforts. The training included three modules on working with individuals, children, and families and was conducted via videoconferencing over three sessions. Assessment of learning needs and collaborative curriculum development are described. Opportunities, challenges, and strategies for cross-cultural training via videoconferencing are discussed.